Prevention of Mother-to-Child Transmission of HIV data completeness and accuracy assessment in health facilities of the Nkangala District - Motlatso G. Mlambo; Karl Peltzer; Annariina Koivu (AOSIS, 2014)
Background: Even though significant progress has been made in the roll-out and quality of the prevention of mother-to-child transmission of HIV (PMTCT) services in South Africa, the quality of patient data recording remains a challenge. Objectives: To assess PMTCT data completeness and accuracy at primary healthcare level to district level in order to assist with the improvement of the PMTCT data recording. Methods: This is a retrospective record review study which involved collecting PMTCT data on indicators which was for the period of August 2009 to January 2010. We conducted baseline facility assessments which included 72 PMTCT sites in one health district, Nkangala. We assessed the data completeness and accuracy of the data values recorded on the seven PMTCT data elements. Results: Data were only complete for less than a quarter of the time for most of the antenatal indicators (0.5% - 44%) and for the maternity indicators, data were only complete 11% of the time. Data inaccuracy was a result of recording of data values in the District Health Information System (DHIS) which were not within 10% of the data values recorded in the case registers. The results show that data were missing from the case registers, monthly summary sheets and DHIS between 30% and 99% of the time and that data elements had values recorded in the DHIS which were > 10%. Conclusion: There is a need for ongoing training on data recording procedures at all levels. To maintain data quality, healthcare data must be appropriate, organised, timely, available, accurate and complete.